Felicity Conditions and Persuasion: A Speech Act Analysis of Presidential Debate Performances - Anggawirya, Arin Mantara; Widayanto, Yuli; Marnina, Marnina; Reliubun, Abdurrahman Shaleh (ITScience (Information Technology and Science), 2025)
This study examines the use of speech acts in persuasive communication during presidential election debates by analyzing how locutionary, illocutionary, and perlocutionary acts operate within political discourse and shape public responses. Using a descriptive qualitative approach, the research draws data from official debate transcripts and audience reactions on platform X, focusing on how utterances function pragmatically and how audiences interpret or resist the intended messages. The analysis employs Austin’s and Searle’s speech act theory, supported by the felicity condition framework, to identify persuasive strategies embedded in assertive, directive, commissive, expressive, and declarative acts. Debate utterances were transcribed, categorized, and compared with public responses to determine whether the perlocutionary effects aligned with or diverged from the intended illocutionary force. Findings reveal a dominant use of assertive acts in shaping arguments and influencing public perception, although the degree of perlocutionary success varied across topics. Audience responses reveal that felicity conditions—particularly propositional content, sincerity, and essential conditions—play a crucial role in determining whether persuasive attempts succeed or result in misunderstanding, resistance, or rejection. Positive alignment between illocution and perlocution emerged when messages were perceived as credible and contextually grounded. In contrast, infelicities occurred when audiences doubted the intentions, accuracy, or feasibility of the claims presented. Overall, the study underscores the centrality of speech acts in shaping persuasive political discourse and demonstrates how public interpretation significantly impacts the effectiveness of persuasive communication in electoral contexts.